2014
DOI: 10.3174/ajnr.a3934
|View full text |Cite
|
Sign up to set email alerts
|

Time-Shift Homotopic Connectivity in Mesial Temporal Lobe Epilepsy

Abstract: BACKGROUND AND PURPOSE:Voxel-mirrored intrinsic functional connectivity allows the depiction of interhemispheric homotopic connections in the human brain, whereas time-shift intrinsic functional connectivity allows the detection of the extent of brain injury by measuring hemodynamic properties. We combined time-shift voxel-mirrored homotopic connectivity analyses to investigate the alterations in homotopic connectivity in mesial temporal lobe epilepsy and assessed the value of applying this approach to epileps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 39 publications
(62 reference statements)
0
18
0
Order By: Relevance
“…Seizure recurrence was associated with a less lateralized functional connectivity pattern than seizure freedom, suggesting that high laterality (i.e., stronger functional connectivity in the ictal hemisphere) predicted better outcome. More recently, Xu et al [63] found that compared with poor outcomes, a successful surgical outcome in TLE was associated with larger interhemispheric homotopic functional connectivity differences. Unfortunately, based solely on rsFC, the number of studies investigating the prediction of seizure outcome following anterior temporal lobectomy remains small.…”
Section: Presurgery Functional Connectivity: Added Value As a Predictmentioning
confidence: 98%
“…Seizure recurrence was associated with a less lateralized functional connectivity pattern than seizure freedom, suggesting that high laterality (i.e., stronger functional connectivity in the ictal hemisphere) predicted better outcome. More recently, Xu et al [63] found that compared with poor outcomes, a successful surgical outcome in TLE was associated with larger interhemispheric homotopic functional connectivity differences. Unfortunately, based solely on rsFC, the number of studies investigating the prediction of seizure outcome following anterior temporal lobectomy remains small.…”
Section: Presurgery Functional Connectivity: Added Value As a Predictmentioning
confidence: 98%
“…Nevertheless, in the last years, new promising predictors of clinical outcomes in refractory TLE have been described based on pre-surgery MRI measures. For instance, using resting-state functional connectivity, Xu et al (2014) found that compared with poor outcomes, a successful surgical outcome in TLE was associated with larger interhemispheric homotopic functional connectivity (FC) differences, pre-surgery. Using structural imaging techniques, recurrent post-surgical seizures have been associated with atrophy in multiple areas such as the thalamus ( Keller et al, 2015a ; Keller et al, 2015b ), temporopolar, and insular cortices, ( Bernhardt et al, 2010 ; Bernhardt et al, 2015 ), along with abnormal white matter tracts emerging from the thalamus ( Keller et al, 2015b ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings prompt interests in the physiological mechanisms underlying functional homotopy. In a range of brain disorders, including schizophrenia 23 24 , autism 25 , major depressive disorder 26 , mesial temporal lobe epilepsy 27 , cocaine addiction 28 and functional dyspepsia 29 , alterations in bilateral connectivity have been identified using the VMHC index, suggesting that it is a valid indicator of inter-hemispheric connectivity changes in aging and diseases ( http://fcp-indi.github.io/docs/user/vmhc.html ).…”
mentioning
confidence: 99%